Implementation of Mobile Cre-Tourism VER.2 Technology as Interactive Learning Media at Tourism Polytechnic - Ida Bagus Putu Puja; Mahendra Adi Winatha; Putu Ayu Aryasih (Universitas Negeri Malang, 2025)
Exploration of the implementation of mobile technology as an interactive learning media in the Tourism Polytechnic has not been used optimally. The purpose of this study is to explore the learning experience of students in understanding tourism materials through the use of smartphone-based applications. The methodology applied includes the development of AR applications specifically designed for learning materials with a development design using the UTAUT2 method, followed by testing its effectiveness through a questionnaire with a Likert scale with a quantitative approach with multiple linear regression analysis and analysis of student learning experience using the application with a qualitative approach using EFAS/IFAS SWOT analysis. The research revealed that students using a smartphone-based application showed significantly improved learning experiences. Data analysis indicated that 91.1% of respondents used their phones daily, and a majority reported increased motivation and engagement due to the interactive nature of the AR application, which facilitated a better understanding of complex tourism concepts. However, challenges such as varying comfort levels with technology among students and limited access to necessary devices were identified as factors that could hinder the effectiveness of AR in enhancing educational experiences